2021
DOI: 10.1136/rapm-2020-102017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and technical factors associated with knee radiofrequency ablation outcomes: a multicenter analysis

Abstract: BackgroundThere has been a surge in interest in radiofrequency ablation (RFA) of the genicular nerves over the past decade, with wide variability in selection, technique and outcomes. The aim of this study is to determine factors associated with treatment outcome.MethodsWe retrospectively evaluated the effect of 23 demographic, clinical and technical variables on outcomes in 265 patients who underwent genicular nerve RFA for knee pain at 2 civilian and 1 military hospital. A primary outcome was designated as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 35 publications
(27 reference statements)
9
23
0
Order By: Relevance
“…It is important to note that more than half of the patients in their study underwent bilateral GNRFA, suggestive of higher baseline disease burden and lower potential for symptom improvement in their sample. Our results on comparative probability of pain relief were consistent with a previous retrospective study which reported that the use of c-RFA, when compared with t-RFA, was associated with a 16% decrease in percentage pain reduction (p=0.03), even though another study showed the opposite association 27 28…”
Section: Discussionsupporting
confidence: 91%
“…It is important to note that more than half of the patients in their study underwent bilateral GNRFA, suggestive of higher baseline disease burden and lower potential for symptom improvement in their sample. Our results on comparative probability of pain relief were consistent with a previous retrospective study which reported that the use of c-RFA, when compared with t-RFA, was associated with a 16% decrease in percentage pain reduction (p=0.03), even though another study showed the opposite association 27 28…”
Section: Discussionsupporting
confidence: 91%
“…As such, we assumed that only patients in the CRFA arm received GNB and accrued the costs. While discussions continue about the need for one or two GNBs, recent data reaffirm that favourable, consistent, and durable treatment outcomes can be achieved following a single GNB with ≥50% relief [ 22 , 27 , 36 ]. Modification of the cost assumptions to reflect real-world clinical practice, including in-office HA administration without ultrasound guidance (versus an outpatient facility using ultrasound) and in-office GNB for CRFA patients (versus outpatient consultation), did not change the overall conclusion that CRFA is cost effective versus HA.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 35 , 36 The cadaver study of Fonkoue et al 36 proposes revised anatomical landmarks for the original genicular nerves. Chen et al 37 and McCormick et al 35 advocate that ablation of up to ten genicular nerves could improve outcomes of this treatment. Future clinical trials incorporating this improved knowledge of the innervation of the knee are necessary for optimalization of the RF technique for chronic knee pain.…”
Section: Discussionmentioning
confidence: 99%